1998
DOI: 10.1046/j.1365-2559.1998.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin and calretinin: a useful combination of immunochemical markers for differentiation between mesothelioma and metastatic adenocarcinoma

Abstract: The combination of E-cadherin/calretinin appears to be a suitable panel for distinguishing metastatic carcinomas and mesotheliomas in pleural lesions. The additional value of other markers is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
98
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 23 publications
9
98
1
Order By: Relevance
“…3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies. 8,16,18,22,25,26,31 A total of 12 (40%) of the squamous carcinomas in the current study exhibited calretinin positivity and even though the staining was focal in most instances, in three of the cases, it was strong and diffuse.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies. 8,16,18,22,25,26,31 A total of 12 (40%) of the squamous carcinomas in the current study exhibited calretinin positivity and even though the staining was focal in most instances, in three of the cases, it was strong and diffuse.…”
Section: Discussionmentioning
confidence: 66%
“…16,17 In 1996, Doglioni et al 16 reported strong calretinin expression in all 36 epithelioid mesotheliomas, but only focal staining was found in 28 (10%) of 294 adenocarcinomas of various origins and in 10 (18%) of 55 squamous carcinomas also of various origins. While many subsequent investigations have confirmed the usefulness of calretinin immunostaining in the differential diagnosis between mesotheliomas and lung adenocarcinomas, 8,[18][19][20][21][22][23][24][25][26][27][28][29] only a relatively few studies have been published on the expression of this marker in squamous carcinomas of the lung. 3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calretinin is expressed in both the cytoplasm and nucleus. According to the literature, its expression in malignant mesothelioma varies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but most authors report frequent expression in epithelioid malignant mesothelioma, with only few studies reporting expression below 90%. Interestingly, calretinin expression has been described in a wide variety of cells, including steroid-producing cells of the testis and ovary, adipocytes, eccrine-glands, keratinizing thymic epithelial cells and numerous tumors, for example Merkel cell carcinoma, Leydig cell tumors of the testis, esthesioneuroblastoma, adenomas of the adrenal gland, small cell carcinoma of the lung and adenomatoid tumor.…”
mentioning
confidence: 99%
“…The few publications that have evaluated calretinin expression in the three most frequent types of malignant mesothelioma separately present data that diverge from 18 to 100% positivity in sarcomatoid malignant mesothelioma, and 8 to 100% in biphasic malignant mesothelioma. 5,7,15,[18][19][20]33 The D2-40 staining frequency is also controversial in sarcomatoid and biphasic malignant mesothelioma. Whereas Chu et al 23 reported staining in all types of malignant mesothelioma, Ordóñ ez 24 did not detect any D2-40 staining in either sarcomatoid malignant mesothelioma or sarcomatoid areas of biphasic malignant mesothelioma.…”
mentioning
confidence: 99%